Cover Image, Volume 8, Issue 2. (15th February 2018) - Hu, Xixi; Zhou, Linsen; Xie, Daiqian
Abstract : The cover image, by Xixi Hu et al., is based on the Advanced Review State‐to‐state photodissociation dynamics of the water molecule, DOI: 10.1002/wcms.1350 . Abstract : The cover image, by Xixi Hu et al., is based on the Advanced Review State‐to‐state photodissociation dynamics of the water molecule, DOI: 10.1002/wcms.1350 .